Analisa pengaruh variasi arus pengelasan GTAW pada baja AISI 1050 terhadap sifat fisik dan mekanis - T. Juwandi; Jenne Syarif; zulkiflli zulkiflli (Journal of Welding Technology, 2021)
Analysis of the effect of variations in welding current GTAW on AISI 1050 steel on physical and mechanical properties, the aim of research is to determine the stress strength, strain and see to determine the character or treatment of AISI 1050 steel. The welding process is closely related to defects that affect its mechanical properties. In this study, the welding process was carried out under the hands of the IASI 1050 material with a thickness of 12 mm with an AWS ER70S-6 electrode with a diameter of 1.2 mm with a current variation of 110 amperes, 120 amperes and 130 amperes with tests carried out are tensile and microstructure testing. From the results of the tensile test, it can be concluded that the tensile stress on the 110 amper specimen is 83.34 kgf/mm2, and the tensile voltage at 120 amperes is 43.45 kgf / mm2, and the tensile voltage at 130 amperes is 67, 97 kgf/mm2 that the higher the welding current, the more ductile the tensile strength value and the greater the welding current, the rougher the surface metallography results.